2010
DOI: 10.1007/s12098-010-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Communication DEALL—An Indigenous Early Intervention Program for Children with Autism Spectrum Disorders

Abstract: Thus, the Communication DEALL program shows promise as an effective early intervention program. It also indicates a need to further enhance the stabilization of the pre linguistic skills such as maintenance of eye contact, attention, sitting tolerance and compliance, in the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 7 publications
0
38
0
1
Order By: Relevance
“…In the study done to develop the COM DEALL programme the authors found that the intervention helped in improving communication as well as the cognitive deficits to some extent [27]. Our study is important as it is one of the few studies which has systematically looked at the communication and language in autistic children, mentally retarded children and children having both as co morbidity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the study done to develop the COM DEALL programme the authors found that the intervention helped in improving communication as well as the cognitive deficits to some extent [27]. Our study is important as it is one of the few studies which has systematically looked at the communication and language in autistic children, mentally retarded children and children having both as co morbidity.…”
Section: Discussionmentioning
confidence: 81%
“…The goal of the programme is to integrate these children into regular schools by school entry age, i.e., 6 years. The Communication DEALL Developmental Checklist (CDDC) was developed by Karanth, to carry out assessments of the children enrolled into the Communication DEALL programme [25,27]. The CDDC is a criterion referenced checklist, to assess developmental skills in 8 domains namely, gross and fine motor skills, activities of daily living, receptive and expressive language skills, and cognitive, social and emotional skills.…”
Section: Subject and Methodsmentioning
confidence: 99%
“…The “Rapid Prompting Method” (RPM), described in two manuals (Iversen, 2007; Mukhopadhyay, 2008) and web sites 1 and taking inspiration from the Communication DEALL 2 early intervention programme (Karanth et al, 2010), is a parent-developed educational therapy for persons with autism who do not speak or who have difficulty using speech communicatively. RPM exploits and develops a rhythmic mode of responding in which the disconnection amongst cognitive goal, affective motive, motor plan, and action becomes less significant because the motor action already is programmed as part of an ongoing rhythm of movements.…”
Section: Introductionmentioning
confidence: 99%
“…The teaching material (i.e., arithmetic, reading comprehension, geography) can come from general educational curricula; however, the method of teaching must be individualised to each child’s initial abilities (Karanth et al, 2010). During the initial sessions, the therapist aims to assess the child’s strengths in terms of preferred channels of sensory perception.…”
Section: Introductionmentioning
confidence: 99%
“…The 'Communication DEALL Developmental Checklists' (CDDC) (Karanth 2007) is another indigenous accompaniment to an early intervention program (Karanth et al 2010) for children with ASD. It covers assessment of eight domains in developmental skills for children up to 6 years and carries local norms.…”
mentioning
confidence: 99%